2006
DOI: 10.1055/s-2005-858870
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss geometrisch-optischer Täuschungen auf sakkadische Augenbewegungen

Abstract: Changes in length perception by visual illusions correspond with changes in the amplitude of saccadic eye movements. Therefore, recordings of saccadic eye movements offer the opportunity to assess changes in visual object perception based on changes of central image processing at the cortical level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…If the availability of online visual feedback is critical, one would predict substantial illusion effects on saccades. Finally, studies on illusion effects on saccades show a large variability in results, ranging from 20–30% (Bernardis et al 2005 ; De Grave et al 2006b ; Knox 2006 ; Lavrysen et al 2006 ; McCarley et al 2003 ) to effects between 10 and 20% (De Grave et al 2006b ; Ehresman et al 2008 ; Festinger et al 1968 ; Lavrysen et al 2006 ; Thompson and Westwood 2007 ) or even less than 10% (Binsted and Elliott 1999 ; McCarley et al 2003 ; Tegetmeyer and Wenger 2004 , 2006 ). Finally, Wong and Mack ( 1981 ) reported that saccadic eye movements were not affected by an illusion of displacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the availability of online visual feedback is critical, one would predict substantial illusion effects on saccades. Finally, studies on illusion effects on saccades show a large variability in results, ranging from 20–30% (Bernardis et al 2005 ; De Grave et al 2006b ; Knox 2006 ; Lavrysen et al 2006 ; McCarley et al 2003 ) to effects between 10 and 20% (De Grave et al 2006b ; Ehresman et al 2008 ; Festinger et al 1968 ; Lavrysen et al 2006 ; Thompson and Westwood 2007 ) or even less than 10% (Binsted and Elliott 1999 ; McCarley et al 2003 ; Tegetmeyer and Wenger 2004 , 2006 ). Finally, Wong and Mack ( 1981 ) reported that saccadic eye movements were not affected by an illusion of displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that position and vector coding are performed by separate mechanisms (De Grave et al 2004 ) one might expect differences in illusion effects. Indeed, studies in which the spatial location of the stimulus was predictable (Binsted and Elliott 1999 ; Ehresman et al 2008 ; Lavrysen et al 2006 ; Tegetmeyer and Wenger 2004 , 2006 ; Thompson and Westwood 2007 ) showed smaller illusion effects than studies in which the stimulus was presented randomly in one of several directions (Bernardis et al 2005 ; De Grave et al 2006a , b ; Knox 2006 ; McCarley et al 2003 ). To systematically investigate the effect of spatial predictability of the stimulus, we asked participants to perform three blocks of trials.…”
Section: Introductionmentioning
confidence: 99%